Seasonal Variation in Thermal Biology and Water Balance in a Year-Round Active Neotropical Treefrog, Scinax fuscovarius - Maenaka, Beatriz M. [UNESP]; Senzano, Luis M. [UNESP]; Andrade, Denis V. [UNESP] (Herpetologists League, 2023)
Because of ectothermy and the high permeability of their skin, the thermal biology and water balance of anuran amphibians are highly influenced by variations in environmental temperature and water availability. Seasonal variation in these climatic variables are often followed by concurrent adjustments in frogs' thermal biology and water balance. We investigated seasonal variation in the thermal biology and water balance of snouted treefrogs, Scinax fuscovarius (Anura, Hylidae), a midsize nocturnal treefrog with continuous activity throughout the year. We measured body temperature when active in the field (T-field), thermal preference (T-pref) in a thermal gradient in the laboratory, and the minimum and maximum critical temperatures (CTmin and CTmax, respectively). Regarding water balance, we measured rates of evaporative water loss (EWL) and the skin resistance (R-s) to evaporation at three temperatures (15, 25, and 35 degrees C), dehydration tolerance, and rates of water uptake (WU), both at 25 degrees C. Measurements were carried out in the middle of the hot and wet spring-summer and the cold and dry autumn-winter. We found that T-field, T-pref, dehydration tolerance, and WU were higher in the hot-wet compared to the cold-dry season. Evaporative water loss rates increased with experimental temperature but did not vary seasonally. There was no seasonal variation in thermal tolerance for either CTmax or CTmin. Our data show that S. fuscovarius experience seasonal adjustments in some parameters of their thermal biology and water balance, but not in others. This variation may reflect different levels of plasticity among the sampled variables and quite likely functional compromises between body temperature regulation and water balance.
Keywords: Amphibian; Animal physiology; Seasonality; Wet-dry neotropics